Caos e termalização na teoria de Yang-Mills-Higgs em uma rede espacial - Fariello, Ricardo Francisco [UNESP] (2009)
In this thesis, we are dedicated to study the time evolution generated by the hamiltonian of a classical Yang-Mills-Higgs theory with gauge symmetry SU(2) on a spatial lattice. In particular, we study energy transfer and equilibration processes among the gauge and Higgs sectors, calculate the maximal Liapunov exponents regarding to random initial conditions in the regime of weak coupling, where one expects them to be related to the high-temperature static plasmon damping rate, and investigate their energy and Higgs self-coupling parameter dependence. We further examine finite-time and finite-size errors, value the impact of the Higgs fields on the instabilty of constant non-abelian magnetic fields and comment on the implications of our obtained results for the thermalization properties of gauge fields at finite temperature in the presence of matter.